An Integrated Approach for Sustainable Supplier Selection in Fuzzy Environment - ŞENOCAK, Ahmet Alp; GÖREN, Hacer GÜNER (International Journal of Intelligent Systems and Applications in Engineering, 2016)
The term sustainability, which means maintaining a balance or acting responsibly for the future, has come into prominence in many fields. One of the most crucial practice is cooperating with convenient collaborators and composing effective supply chains in terms of social, economic and environmental considerations. Therefore, sustainable supplier selection is getting more and more important to compete in rapidly changing environment. To deal with sustainable supplier selection problem, this study aims to determine the selection of appropriate suppliers and allocation of orders to them. The proposed approach operates in three stages. In the first stage, Fuzzy Decision Making Trial and Evaluation Laboratory is used to obtain the weights of the criteria from sustainability perspective. In the second stage, by using Fuzzy Grey Relational Analysis, a set of suppliers are ranked and their suitability scores are calculated. In the last stage, optimal order quantities to be procured by the suppliers are obtained via fuzzy linear programming including imprecise data of demand, error rate and capacity.